Kollokasies: ’n Leksikografiese perspektief - van Niekerk, A.E. (Lexikos, 1992)
Collocations: A Lexicographical Perspective It is the responsibility of the lexicographer to give an account of collocations in a monolingual explanatory dictionary. Collocations are unpredictable conventionalized sintagmatic combinations and could therefore only be acquired through learning. The native speaker will not necessarily be able to anticipate a particular collocational pattern intuitively. In accordance with the cognitive approach a clear distinction can not be drawn between free phrases, collocations and idioms. The lexicographer should nevertheless be able to justify his distinction within the context of the dictionary. The needs of the dictionary user should always be adhered to. The lexicographical function of collocations is different from, but supplementary to those of the definition and the examples respectively. Therefore collocations have a unique position within the linear microstructure which neither the definition nor the examples can replace. The semantic differentiation between base and collocator is of little importance to the lexicographer. A collocation can potentially be included in the article of either the base or the collocator. The detection of collocational patterns can be simplified by the use of a computer. Thus the task of the lexicographer will be eased considerably. In supplying collocational information the lexicographer gives substance and structure to the dictionary article. The user will, in addition, benefit from a complete, well-founded treatment of collocations.